Nuevos registros del Águila Coronada (Harpyhaliaetus coronatus) para cuatro provincias argentinas - Barrionuevo, Carlos; Fra, Enrique; Salinas, Roberto; Ortiz, Diego; Julio, Luis; Capllonch, Patricia; Aráoz, Rodrigo (Nuestras Aves, 2011)
Este artículo no cuenta con un resumen.